EXPERIENCE OF ADALIMUMAB ADMINISTRATION TO A PATIENT WITH JUVENILE ANKYLOSING SPONDYLOARTHRITIS AND CHRONIC VIRUS HEPATITIS B - E. A. Legostaeva; V. Yu. Avdeenko; I. A. Tsyganok; E. A. Besedina; N. A. Tsurikova; N. N. Kobzeva (Union of pediatricians of Russia, 2014)
The article presents a clinical case of high effectiveness of adalimumab - human monoclonal antibodies to tumor necrosis factor - in a patient with juvenile ankylosing spondyloarthritis refractory to therapy with classic immunosuppressive drugs and secondary to virus hepatitis B in the integrative phase. Joint pains and intensity of exudative alterations in interphalangeal and wrist joints attenuated as early as after as the first adalimumab injection; the authors achieved a 50% improvement in indices BASDAI (2.4) and ASDAI (1.1). Acute inflammatory alterations terminated, motion range of the affected joints completely recovered, general laboratory parameters of disease activity (erythrocyte sedimentation rate, C-reactive protein and white blood cell count) normalized and inactive disease stage was registered after 6 months. Adverse events or virus hepatitis B exacerbations in the setting of adalimumab therapy were not observed. No osteochondral destruction progression was observed at computed and magnetic resonance imaging of joints 6 months after the therapy beginning. Emotional condition and quality of life of the child and his family improved considerably.